David Copperfield abridged: Transformations of the novel in Russian translations - E. I. Samorodnitskaya (Шаги)
Despite the fact that the Russian reception of Charles Dickens and translations of his novel The Personal History, Adventures, Experience and Observation of David Copperfield the Younger of Blunderstone Rookery (Which He Never Meant to be Published on any Account) has already become an object of research, analysis of translations of the novel adapted for children’s reading is still far from being complete and systematic. The article attempts to compare three translations of the novel by E.G. Beketova, M.I. Lovtsova and A.A. Beketova, published in the first half of the twentieth century and addressed to a children’s audience. While E.G. and A.A. Beketova adhere to the principles of literalism and strive to preserve both the author’s humor and the specificity of the characters, the cuts in Lovtsova’s translation cause a simplification of the images of the novel’s central characters, and the result is an outline of the novel, an adapted and truncated retelling. The translator ignores wordplay, episodes and plot lines that complicate the characters’ images, the mention of David’s unborn sister existing in Betsy Trotwood’s imagination and fitting the old lady into Dickens’ gallery of sensible cranks. A young reader may find such a text easier to cope with, but it is hardly interesting. Both Beketovas’ translations are closer to Dickens’ poetics, which cannot be reduced exclusively to an adventure novel in a melodramatic spirit.